Advocating Education on Information Security Critical Thinking using Social Network: A Model - Kartikawangi, Dorien; Lukas (Archives of Business Research, 2025)
Digital dilemma causes a world of volatility, uncertainty, complexity, and ambiguity (VUCA). This paper aims to elucidate the education of users on security-critical thinking to prevent and cope with VUCA (Volatile, Uncertain, Complex, and Ambiguous) challenges caused by ICT. From an engineering perspective, information security involves maintaining the confidentiality, integrity, and availability of information. Based on this theory, a quantitative and qualitative approach is employed, utilizing surveys and observations for data collection. Research findings suggest that understanding security is essential, and effective communication becomes central to critical thinking and the advocacy of information security. Here, communication serves as a form of education in information security, amplifying and disseminating critical thinking to the public. The quantitative results explain that educational background and cohort have unique characteristics in information security at the cognitive, affective, and behavioral levels. The qualitative results show that informal education provided by NGOs and the Government is not explicitly focused on critical thinking regarding information security, but rather more general and delivered massively. Based on these findings, this paper proposes a model of critical thinking in information security education, which consists of three elements: confidentiality, integrity, and availability of information, referred to as ISCT-CIA.